New Method for Optimal Conductor Selection of Radial Distribution Network - Kumar, Sailesh V.K. (My University, 2008)
The optimum planning of power distribution networks is one of the most important research fields for electrical engineers. That is because of the close proximity of these networks to the ultimate consumers. Normally in distribution system operational costs are high because of their losses. The ultimate aim of this thesis work is to plan distribution networks which satisfy the growing demand for electricity, fulfill specific technical operational constraints and which are also characterized by the minimum overall cost. In this thesis work a simple and efficient method for optimal conductor selection of radial distribution networks. The proposed method also shows that only proper selection of optimum branch conductors reduces losses instead of using uniform conductors. The usefulness of the proposed method is demonstrated by two examples, 16 node, 31 node radial distribution network.
M.E. (Power Systems and Electric Drives)
Keywords: Optimal conductor, radial distribution network